Undertaking a business or not? Which is the best option? Analysis of the entrepreneurial intention profile of employees of startups and information technology companies in Rio Grande do Sul - Rosa, Juliana Ribeiro da; Fleck, Carolina Freddo (REGEPE Entrepreneurship and Small Business Journal, 2021)
Purpose: to investigate the entrepreneurial intention profile of the employees of startups and small companies in the technology segment of the State of Rio Grande do Sul, when they working to an organization. Methodology: descriptive research, using a quantitative approach, using the survey method. The data collection instrument was the questionnaire, based on the model by Kristiansen & Indarti (2004). Findings: the results demonstrate that more than 60% of the respondents intend to undertake, especially when perceiving themselves as a desired professional in the job market. Theoretical contributions: the study contributes theoretically to studies of entrepreneurial intent in Brazil, mainly because it provides a view outside the sphere of higher education institutions, the setting for most of the studies already published. Originality: when conducting a survey of data on Startups and Small Companies in the Technology segment, in the State of Rio Grande de Sul, it was found a small number of employees involved in the operations of these businesses, but with a good percentage interested in undertaking. Contributions to management: the study contributes to the advance of management in the sectors of startups and the technology area of Rio Grande do Sul, by identifying that incentive work and skills development can generate new business partnerships within the startups themselves, generating growth and competitive potential. JEL Code: M00, M10, M13, M15 e M59